Adherence to Brain Trauma Foundation guidelines for management of traumatic brain injury patients: study protocol for a systematic review and meta-analysis. Issue 1 (December 2015) - Khormi, Yahya; Gosadi, Ibrahim; Campbell, Sandra; Senthilselvan, Ambikaipakan; O'kelly, Cian; Zygun, David
Abstract Background Traumatic brain injury (TBI) is a leading cause of death and disability around the world. Management based on Brain Trauma Foundation (BTF) guidelines is widely accepted and thought to improve outcome. The objectives of this systematic review are to give an overview of adherence to the BTF guidelines, describe factors influencing adherence, and study the effect of guideline-based management on outcome. Methods/design We will search electronic bibliographic databases: PROSPERO, Medline, EMBASE, SCOPUS, NHS, CINAHL, Cochrane Database, and ProQuest Dissertations and Theses Global. Two investigators will independently screen all titles, abstracts, and articles and select Randomized Controlled Trial (RCT), cohort studies, case-control studies, and case series reporting the adherence rate, factors influencing adherence, and mortality or morbidity. These investigators will also independently extract data using a pre-designed and pilot-tested standardized electronic data extraction form and assess the risk of bias. We will exclude pediatric and military-related TBI studies, studies that included fewer than ten patients or addressed adherence to pre-hospital guidelines. Narrative synthesis and if appropriate, quantitative meta-analysis clustered by type of recommendation will be reported. Discussion This study is expected to demonstrate the current level of professionals' adherence to BTF guidelines in patients with severe traumatic brain injury, it will describe the factors influencing adherence, which may provide valuable input for development of strategies to successfully increase adherence. In addition, if the studies are sufficiently homogenous, it will describe the effect of these guidelines on patient outcome. Systematic review registration PROSPEROCRD42015017794